2017
DOI: 10.1111/jth.13667
|View full text |Cite
|
Sign up to set email alerts
|

Once versus twice daily aspirin after coronary bypass surgery: a randomized trial

Abstract: Background Acetyl-salicylic acid (ASA) hyporesponsiveness occurs transiently after coronary artery bypass graft (CABG) surgery and may compromise the effectiveness of ASA in reducing thrombotic graft failure. A reduced response to ASA 81 mg once-daily after CABG surgery is overcome by four times daily ASA dosing. Objectives To determine whether ASA 325 mg once-daily or 162 mg twice-daily overcomes a reduced response to ASA 81 mg once-daily after CABG surgery. Methods Adults undergoing CABG surgery were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Our results show that although there is an early increase in all 3 markers post-CABG, the rise in IPC continued for at least 6 days and tracks closely with the rise in platelet count. 3,4,7 This observed correlation between the elevation in IPC and rise in platelet count is promising as it indicates that by identifying reticulated platelets, a hematology analyzer in routine use has the potential to detect a 2fold increase in platelet production.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our results show that although there is an early increase in all 3 markers post-CABG, the rise in IPC continued for at least 6 days and tracks closely with the rise in platelet count. 3,4,7 This observed correlation between the elevation in IPC and rise in platelet count is promising as it indicates that by identifying reticulated platelets, a hematology analyzer in routine use has the potential to detect a 2fold increase in platelet production.…”
Section: Discussionmentioning
confidence: 88%
“…
Recent studies indicate that an increased rate of platelet production (thrombopoiesis) is an important cause of reduced responsiveness to once-daily aspirin. [1][2][3][4][5][6] With accelerated thrombopoiesis, the number of "non-acetylated platelets" in the circulation increases, thereby overcoming the ability of once-daily aspirin to inhibit arachidonic acid-mediated platelet aggregation for up to 24 hours. Identifying accelerated thrombopoiesis is potentially important because the associated reduced pharmacological response is modifiable by administering aspirin twice daily.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in thrombopoietic indexes were largely reversible 3 months after surgery 32. As shown by 3 independent studies, shortening the dosing interval (ie, twice‐daily dosing), but not doubling the dose, safely rescued the impaired antiplatelet effect of low‐dose aspirin and prevented platelet activation associated with acute inflammation and enhanced platelet turnover following cardiac surgery 32, 36, 37…”
Section: Differences In Systemic Inflammatory Reaction and Platelet/cmentioning
confidence: 92%
“…Similar was concluded in a small low-risk cohort patients in which reduced ASA responsiveness as assessed with impedance aggregometry was not associated with increased incidence of major adverse cardiac and thromboembolic events and mortality after CABG surgery [51]. In a randomized trial on 68 patients, it was tested whether more frequent dosing improves ASA response following CABG surgery, and it was noted that twice-daily compared with once-daily dosing reduces ASA hyporesponsiveness after CABG surgery, but the efficacy of twice-daily ASA needs to be tested in a trial powered for clinical outcomes [52]. In comparison, meta-analyses of studies consisting of patients with cardiovascular disease (not only CABG patients) suggested that patients who were resistant to aspirin were at a greater risk…”
Section: Resistance To Antiplatelet Therapy and Its Clinical Significmentioning
confidence: 99%